2010
DOI: 10.1088/0031-9155/55/8/n02
|View full text |Cite
|
Sign up to set email alerts
|

Gating characteristics of an Elekta radiotherapy treatment unit measured with three types of detector

Abstract: Abstract. The characteristics of an Elekta Precise treatment machine with a gating interface were investigated. Three detectors were used: a Farmer ionisation chamber; a MatriXX ionisation chamber array and an in-house, single pulse-measurement ionisation chamber (IVC). Measurements were made of dosimetric accuracy, flatness and symmetry characteristics and duty cycle for a range of beam-on times and gating periods. Results were compared with a standard un-gated delivery as a reference. For all beam-on times, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
(49 reference statements)
0
13
1
Order By: Relevance
“…A separate set of experiments was carried out to investigate whether the depth signal from a Kinect v2 system could be used to gate an Elekta linac via the previously tested Elekta Response ™ gating interface 16, 17. See Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A separate set of experiments was carried out to investigate whether the depth signal from a Kinect v2 system could be used to gate an Elekta linac via the previously tested Elekta Response ™ gating interface 16, 17. See Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that the beam-on delay can be reduced to less than 0.22 s on an Elekta Linac with the use of the Elekta Response™ gating interface. 38,39 The Response interface provides a direct hardware connection to the PRF enable chain of the Linac. It can open or close the physical relays that control beam delivery by use of a TTL input signal.…”
Section: G Latency Of the Systemmentioning
confidence: 99%
“…More recently, the gating characteristics (e.g., beam profile and beam delivery efficiency) have been evaluated for Elekta Precise and Synergy linacs 10, 19. In this study, we have focused on the beam startup characteristics for gated delivery of an Elekta linac and the overall accuracy of the delivery for a variety of gating scenarios.…”
Section: Introductionmentioning
confidence: 99%